Strategic control of myopic best reply in repeated games - Burkhard C. Schipper (University of California, Department of Economics, 2011)
How can a rational player strategically control a myopic best reply player in a repeated two-player game? We show that in games with strategic substitutes or strategic complements the optimal control strategy is monotone in the initial action of the opponent, in time periods, and in the discount rate. As an interesting example outside this class of games we present a repeated textbook-like Cournot duopoly with non-negative prices and show that the optimal control strategy involves a cycle.
Keywords: C70; C72; 330; strategic teaching; learning; adaptive heuristics; dynamic optimization; strategic substitutes; strategic complements; myopic players